I.T. Outsourcing in Malaysia: An Exploratory Study on The Benefits, Risks and Challenges - Chin, Chiu Hsia (2009)
I.T. outsourcing is a global trend that is adopted by many companies. The drivers and benefits of choosing this outsourcing path are many, but the risks and challenges thereto are equally present. Real world experience suggests that outsourcing does not always deliver the anticipated benefits - mixed results have been produced so far. Not much literature has been found related to the studies of I.T. outsourcing practise in Malaysia. In this research, I obtain findings based on several in-depth interviews with key I.T. personnel from the Malaysian companies across various industries, eliciting their valuable insights, opinions and lessons learnt related to their experience in I.T. outsourcing. It is hoped that this research provides valuable insights to both academics and practitioners, on the status of the I.T. outsourcing practise in Malaysia.